2023
DOI: 10.1126/sciimmunol.add4132
|View full text |Cite
|
Sign up to set email alerts
|

pDC-like cells are pre-DC2 and require KLF4 to control homeostatic CD4 T cells

Abstract: Plasmacytoid dendritic cells (pDCs) have been shown to play an important role during immune responses, ranging from initial viral control through the production of type I interferons to antigen presentation. However, recent studies uncovered unexpected heterogeneity among pDCs. We identified a previously uncharacterized immune subset, referred to as pDC-like cells, that not only resembles pDCs but also shares conventional DC (cDC) features. We show that this subset is a circulating precursor distinct from comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 87 publications
2
18
0
Order By: Relevance
“…The original cDC2B population included a small proportion of cells marked by RORγt fate mapping 15 , later shown to constitute a distinct lymphoid cell type rather than bona fide cDCs 16 . In a further study, KLF4-dependent cDC2s were suggested to correspond to cDC2Bs 17 . Finally, infection or cancer can drive the appearance of cells termed ‘inflammatory cDC2s’ and ‘mature dendritic cells enriched in regulatory molecules’, respectively 12 , 18 , 19 .…”
Section: Mainmentioning
confidence: 85%
“…The original cDC2B population included a small proportion of cells marked by RORγt fate mapping 15 , later shown to constitute a distinct lymphoid cell type rather than bona fide cDCs 16 . In a further study, KLF4-dependent cDC2s were suggested to correspond to cDC2Bs 17 . Finally, infection or cancer can drive the appearance of cells termed ‘inflammatory cDC2s’ and ‘mature dendritic cells enriched in regulatory molecules’, respectively 12 , 18 , 19 .…”
Section: Mainmentioning
confidence: 85%
“…2D). We also examined the Cx3cr1 + DC subset that is developmentally related to pDCs and was recently designated as transitional DCs (tDCs) (48)(49)(50)(51). The fraction of tDCs in the spleens of Carm1 Δ chimeras was significantly reduced (Fig.…”
Section: Identification Of Molecular Regulators Of DC Differentiationmentioning
confidence: 99%
“…Their functional versatility makes them attractive for being targeted in vaccination against pathogens or cancer (2-6). Accordingly, considerable work has been invested in understanding the functional and ontogenetic diversity of cDCs, yet these cells remain ambiguous to define as fate mapping has recently uncovered novel populations with overlapping phenotype but distinct origin (2,(7)(8)(9)(10)(11)(12). cDCs are generally considered to descend from committed myeloid cDC progenitors (13)(14)(15) and exist as functionally specialized subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…Both subtypes can induce Th17 responses but cDC2A appear more potent inducers of T follicular helper cell (Tfh) responses (19), while cDC2B may better promote Th2 responses (20). Fetal liver lymphoid progenitors in neonatal spleen and lymphoid derived transitional DCs (tDCs) in adult spleen can differentiate into cells resembling cDC2A and cDC2B (9)(10)(11)21). tDCs are cells with features of both cDCs and plasmacytoid DCs (pDCs), the latter of which are potent producers of type I interferons in response to viruses (9,10,21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation